Actualizations of Maqashid al-shariah in Modern Life: Maqashid al-Shariah Theory As a Method of the Development of Islamic Laws and Shariah Economics - Abdurrohman Kasdi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2019)
This article aims to examine the thoughts of Imam al-Syatibi on maqashid al-shariah and its actualizations in modern life. The method used is qualitative, while the data analysis technique used is content analysis to analyze the substance of maqashid al-shariah. It is then correlated with the context of current human life. The results of the study show that the theory of maqashid al-shariah initiated by Imam al-Syatibi has presented shariah in its elastic face. Maqashid al-shariah has transformed Islamic theory into universal human values, such as benefit, justice, and equality in Muslims' lives in the world. This can be seen at least in two ways: first, maqashid al-shariah as a developing Islamic law method. The development of the theory of maqashid al-shariah has inspired the philosophy of Islamic laws. It becomes the basis of thinking and analysis, which is fundamental to Islamic legal thinking in this globalization era and dynamic social changes. Second, maqashid al-shariah in building shariah economics; maqashid al-shariah's theory occupies a very central and vital position in formulating a shariah economic development methodology. In the context of shariah economics, the purpose of maqashid al-shariah is to safeguard human benefits. A Muslim is encouraged to produce and consume goods/services, of course, within valuable considerations.